On the applicability of Benford law to exoplanetary and asteroid data - Melita, Mario D.; Miraglia, Jorge Esteban (Elsevier, 2021)
In this article we investigate the masses, orbital periods, semimajor axis, eccentricities and radii of the existing exoplanets by comparing the first and second digit probabilities with Benford laws’s predictions. It is found that the masses, orbital periods and semimajor axis conform to Benfordós law quite well, but radii fail. It is also investigated the first digits occurrence corresponding to a given order of magnitude. We introduce a top function which can estimate all the probabilities of the first digit order-to-order.
Keywords: Ley de Benford; Sistemas exoplanetarios; Ciencias naturales::Ciencias físicas::Astronomía